TI_GERICHTE 52.2018.506 vom 26. September 2018 , Docenti cantonali. Passaggio al nuovo modello salariale. Parità di trattamento - TI Tribunale d'appello (2018)
Docenti cantonali. Passaggio al nuovo modello salariale. Parità di trattamento